Characterizing pediatric lung ultrasound findings during a chemically induced bronchospasm. Issue 6 (13th April 2022) - Gagnon, Francois; Marzook, Noah; Deragon, Alexandre; Lands, Larry C.; Zielinski, David; Shapiro, Adam J.; Rampakakis, Emmanouil; Dubrovsky, Alexander S.
Abstract: Background: Lung ultrasound (LUS) has been shown to be a useful clinical tool in pediatrics, but very little is known about the LUS findings of asthma in children. Objectives: The primary objective was to characterize LUS findings of pediatric patients before and after a chemically induced bronchospasm. The secondary objective was to evaluate the effect of bronchodilators on LUS findings. Methods: Eligible children 6−17 years old presenting for a methacholine challenge test (MCT) in a pediatric respiratory clinic were recruited. Patients with viral symptoms were excluded. A six‐zone LUS protocol was performed before and after the MCT, and after bronchodilator administration; video recordings were analysed by an expert blinded to the patient characteristics and MCT results. Results: Forty‐four patients were included in the study. Five patients had positive LUS findings at baseline. Nine patients out of 29 (31%) had new‐onset positive LUS following a reactive MCT. There was a significant association between having a chemically induced bronchospasm and a positive LUS post‐MCT (odds ratio [95% confidence interval]: 5.3 [1.0−27.7]; p = 0.05). Among patients who developed positive LUS findings post‐MCT, four out of nine returned to having a negative LUS postbronchodilator administration. Conclusions: This is the first known report of an association between LUS findings and bronchospasm in pediatric patients. It is also the first documentation of resolution of LUS findings postbronchodilator administration. Most LUS findings observed were small and limited to a few intercostal spaces. Further research is required to quantify these findings and evaluate the effect of salbutamol on LUS.